The value of given expression when m = 3 is 27
Given expression is [tex]3m^2[/tex]
We have to evaluate the given expression for m = 3
To find for m is equal to 3, substitute m = 3 in given expression
From given expression,
[tex]\rightarrow 3m^2[/tex]
Plug in m = 3 in above expression
[tex]\rightarrow 3(3)^2[/tex] ------ eqn 1
We know that,
[tex]a^2[/tex] can be expanded as,
[tex]a^2=a \times a[/tex]
Applying this in eqn 1, we get
[tex]\rightarrow 3(3)^2=3 \times (3 \times 3)[/tex]
Simplify the above expression
[tex]\rightarrow 3(3)^2=3 \times (3 \times 3) = 3 \times 9 = 27[/tex]
Therefore, for m = 3 we get,
[tex]\rightarrow 3(3)^2=27[/tex]
Thus value of given expression when m = 3 is found